2019
DOI: 10.1016/j.clinph.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Methods for analysis of brain connectivity: An IFCN-sponsored review

Abstract: Human brain connectome Connectomics fMRI EEG h i g h l i g h t s There are a variety of technologies valuable for exploring human brain connectivity. The main aspects of anatomical, functional and effective connectivity are described. A multimodality approach can be useful to evaluate the human brain connectome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 333 publications
(374 reference statements)
1
82
0
6
Order By: Relevance
“…Electroencephalography (EEG) and magnetoencephalography (MEG) can be used to analyze functional connectivity (FC) through the analysis of temporal correlations between spontaneous activity of different regions and are characterized by elevated temporal resolution. Functional MRI (fMRI) has a higher spatial resolution and represents the most used approach to explore brain network organization in vivo [12,13]. Resting state-fMRI (rs-fMRI) offers the chance to explore overall brain connectivity in healthy individuals and in different pathological conditions [14,15].…”
Section: Brain Network Organizationmentioning
confidence: 99%
“…Electroencephalography (EEG) and magnetoencephalography (MEG) can be used to analyze functional connectivity (FC) through the analysis of temporal correlations between spontaneous activity of different regions and are characterized by elevated temporal resolution. Functional MRI (fMRI) has a higher spatial resolution and represents the most used approach to explore brain network organization in vivo [12,13]. Resting state-fMRI (rs-fMRI) offers the chance to explore overall brain connectivity in healthy individuals and in different pathological conditions [14,15].…”
Section: Brain Network Organizationmentioning
confidence: 99%
“…As result, confirming the existence of any white matter connection, invasive methods and comparative work is mandatory. Indeed, in-vivo tractography findings are often complemented with comparisons to anatomical knowledge from post-mortem methods, advancing knowledge and discovery (for a discussion about statistical methods for tractography evaluation see also Pestilli 2015Pestilli , 2018Rokem et al 2017;Rossini et al 2019;Takemura et al 2016b). It has been demonstrated that, under certain conditions of scientific rigor, in-vivo tractography helps to clarify the organization of white matter anatomy otherwise left unresolved by post-mortem methods (Takemura et al 2016b;Takemura et al 2019;Wandell 2016;Sani et al 2019;Yeatman et al 2014;Puzniak et al 2019;Takemura et al 2017;Leong et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Graph theory offers a helpful approach to analyzing connectivity data deriving from neurophysiological (i.e., electroencephalography and magnetoencephalography) or imaging (i.e., functional MRI, fMRI) techniques [12][13][14][15][16][17]. Complex brain networks can be modeled as a series of nodes, indicating different brain regions, and edges, representing the connections between nodes.…”
Section: Brain Network Architecture Provides Resilience To Damagementioning
confidence: 99%
“…Complex brain networks can be modeled as a series of nodes, indicating different brain regions, and edges, representing the connections between nodes. The edges are defined on the basis of structural (i.e., diffusion tensor imaging, DTI) or functional connectivity (i.e., temporal covariation of spontaneous activity) between different regions [17][18][19]. Specific measures describing network functioning have been defined.…”
Section: Brain Network Architecture Provides Resilience To Damagementioning
confidence: 99%